2012
DOI: 10.1186/1756-0500-5-198
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative effects of Salacia reticulata leaves hot-water extract on interleukin-1β-activated cells derived from the synovium of rheumatoid arthritis model mice

Abstract: BackgroundSalacia reticulata (SR) is a plant native to Sri Lanka. In ayurvedic medicine, SR bark preparations, taken orally, are considered effective in the treatment of rheumatism and diabetes. We investigated the ability of SR leaves (SRL) to inhibit in vitro the interleukin-1β (IL-1β)-activated proliferation of synoviocyte-like cells derived from rheumatoid arthritis model mice.FindingsInflammatory synovial tissues were harvested from type II collagen antibody-induced arthritic mice. From these tissues, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It is an autoimmune and polyarthritic condition, characterized by inflammation of the synovium (synovitis), progressive cartilage destruction, and bone erosion, which ultimately results in loss of integrity of the affected joints (Lautenbach et al, 2013 ). The RA synovium is enriched with a variety of cell types, including synovial fibroblasts, immune cells (e.g., mast cells, macrophages, neutrophils, dendritic cells, B cells, and T cells; Hitchon and El-Gabalawy, 2011 ), and newly formed blood vessels from the pre-existing vasculature (angiogenesis; Paleolog, 2002 ) (Figure 1 ). Hypoxia is an important micro-environmental characteristic of RA (Lund-Olesen, 1970 ; Hitchon and El-Gabalawy, 2004 ; Gaber et al, 2005 ; Konisti et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is an autoimmune and polyarthritic condition, characterized by inflammation of the synovium (synovitis), progressive cartilage destruction, and bone erosion, which ultimately results in loss of integrity of the affected joints (Lautenbach et al, 2013 ). The RA synovium is enriched with a variety of cell types, including synovial fibroblasts, immune cells (e.g., mast cells, macrophages, neutrophils, dendritic cells, B cells, and T cells; Hitchon and El-Gabalawy, 2011 ), and newly formed blood vessels from the pre-existing vasculature (angiogenesis; Paleolog, 2002 ) (Figure 1 ). Hypoxia is an important micro-environmental characteristic of RA (Lund-Olesen, 1970 ; Hitchon and El-Gabalawy, 2004 ; Gaber et al, 2005 ; Konisti et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is confirmed by literature data, showing that diterpenes cause hemolysis and membrane damage of erythrocytes. [ 37 38 ] Cytotoxic effects of AFEOR are mediated not only by interaction of AFEOR compounds with cell membranes but also by cellular uptake and subsequent activation of necrosis or apoptosis. Therefore, more research is needed by isolating the pharmacologically active compounds from this medicinal oil.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that 5-80 µM Catechin-7,4 -O-digallate from Woodfordia uniflora can also regulate the NF-κB signaling pathway in mouse macrophages and reduce IL-6 and IL-1β levels [320]. On the other hand, Salacia reticulata leaves showed the capacity to inhibit MTS-CH7 cell proliferation (IC 50 score of ~850 µg/mL) [321].…”
Section: Clinical Trialsmentioning
confidence: 99%